Penerapan Aplikasi Kasir Pintar Berbasis Android Untuk Penyajian Laporan Keuangan Pada Usaha UMKM Sarapan Pagi - Nurzam, Nurzam; Kurniawan, Kimas; Ikhsaliana, Tiara; Mahardika, M. Gali; Mutiarani, Nyimas Asti (Universitas Dehasen Bengkulu, 2025)
Sarapan Pagi which is an MSME engaged in the food and beverage business. Established in 2014, the financial records of UMKM breakfast still apply manual recording so that financial management is still not going well, so they do not know whether their business is profitable or loss and cannot control cash flow properly. The implementation of this service is carried out by socializing the use of the Smart Cashier application in Breakfast MSMEs. This community service activity consists of five stages, namely: Identification of application needs, Design, Interview, Implementation Stage, Evaluation of activity results. Based on the socialization carried out, that in recording finances using the Android-based Smart Cashier Application on the Smartphone of MSME owners in the Pantai area, Bengkulu City, it is proven to make it easier in business transactions in the form of sales-purchases, accounts payable, financial reports on Smartphones are easy to use at any time and this application can manage or control cash flow better and can find out that the business is still losing money. Real time information in this system helps operations move more effectively and efficiently. The purpose of the title